EFEK FERMENTASI AMPAS TAHU MENGGUNAKAN Saccharomyces cerevisiae SEBAGAI BAHAN BAKU PAKAN IKAN LELE DUMBO (Clarias gariepinus) - Nugraha, Hilman Fajar; Noerkhaerin Putra, Achmad; Mas, Syamsunarno Bayu (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2023)
Tofu dregs are solid waste obtained from making tofu which can be used as raw material for fish feed because it has high nutritional content and is abundantly available. This study aims to evaluate the effect of S. cerevisiae fermentation on tofu dregs as a raw material for catfish (Clarias gariepinus) feed. This research used a completely randomized design consisting of 3 feed treatments and 3 replications, namely: reference feed treatment (A), tofu waste feed treatment without fermentation (B) and tofu waste feed treatment with fermentation (C). The results showed that fermentation of S. cerevisiae could increase the protein content in tofu dregs. Feeding fermented tofu dregs provides higher protein digestibility, dry matter digestibility, raw material digestibility and growth rate for catfish compared to test feed without fermentation. Apart from that, tofu dregs fermented by S. cerevisiae have the potential to be used as raw material for catfish feed.